Road Network as the Basic Factor of Integrating Croatia Into the Traffic System of 21st Century Europe - Županović, Ivo; Štefančić, Gordana; Vurdelja, Joso (Promet - Traffic&Transportation, 2012)
Transportation of cargo and people, i.e. freight and passengerflows, belongs to the inevitable destiny of the humanity. Inmodem life and overall economic international integration, therole and significance of transportation branch is multiply complex,because free circulation of goods, people, capital and information,etc. are no longer a phenomenon which only followsthe found needs, but it represents a hypothesis of the overall developmentof a certain area. In the presence of the tendency towardsglobalisation of the humanity, increasing emphasis is puton the concentration of the transportation efficiency at certaintraffic corridors defined by favourable geographic and otherconditions for creating optima/traffic system. Defining of certaintraffic corridors is mainly carried out on the basis of trafficand transit conditions of the considered region (usually a country),as well as its physical infrastructure connections with theneighbouring communities.This logically leads to the following questions: Will croatia,when, in which way and to what extent, succeed in securing herplace in the traffic network of the 21st century europe?!The discussion regarding possible answers to these questionsis in fact the main topic of this paper.